2018
DOI: 10.3389/fimmu.2018.00583
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Tumor Necrosis Factor Receptor Type II in CD8+ Regulatory T Cells and CD8+ Effector T Cells

Abstract: Tumor necrosis factor (TNF) is a pleiotropic cytokine that has both pro-inflammatory and anti-inflammatory functions. The biological functions of TNF are mediated by two receptors, TNF receptor type I (TNFR1) and TNF receptor type II (TNFR2). TNFR1 is expressed universally on almost all cell types and has been extensively studied, whereas TNFR2 is mainly restricted to immune cells and some tumor cells and its role is far from clarified. Studies have shown that TNFR2 mediates the stimulatory activity of TNF on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 94 publications
1
55
0
Order By: Relevance
“…TNFR2, also known as p75, is preferentially expressed on endothelial and hematopoietic cells, and some tumor cells. The subsequent pathways at this time are not as well delineated as those for TNFR1, but ongoing studies suggest TNFR2 mediates the activity of regulatory and effector CD8+ T cells, as well as interleukin production by B cells [3,4]. In the eye, pigment epithelial cells of the iris, the ciliary body, and retina locally express TNFR1 and TNFR2.…”
Section: Stimulation Of a Tnf-producing Cell (Top) Results In Cell Sumentioning
confidence: 99%
“…TNFR2, also known as p75, is preferentially expressed on endothelial and hematopoietic cells, and some tumor cells. The subsequent pathways at this time are not as well delineated as those for TNFR1, but ongoing studies suggest TNFR2 mediates the activity of regulatory and effector CD8+ T cells, as well as interleukin production by B cells [3,4]. In the eye, pigment epithelial cells of the iris, the ciliary body, and retina locally express TNFR1 and TNFR2.…”
Section: Stimulation Of a Tnf-producing Cell (Top) Results In Cell Sumentioning
confidence: 99%
“…All of these proteins are involved in the regulation of inflammatory pathways. TNFRSF1B is implicated in T‐cell‐mediated immune responses . MMP3 is an important downstream activator of MMPs, including MMP9 which is implicated in the cleavage of ITGB2 leading to exodus of macrophages from the area of inflammation, which is vital in limiting the local innate immune response .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our high-parameter analysis also revealed a Treg subset producing increased TNF-α and NKT cells producing increased IL-2 in response to anti-PD-1 therapy. The role of TNF-α as an antitumor molecule and a stimulator of adaptive immunity is well established (22)(23)(24)(25). Recent studies, however, have demonstrated that Tregs are maintained by TNF-α via TNF receptor 2 (26) and themselves produce TNF-α in response to activation, providing an autocrine immune-suppressive effect (27).…”
Section: Discussionmentioning
confidence: 99%